2022
DOI: 10.1038/s41598-022-13885-9
|View full text |Cite
|
Sign up to set email alerts
|

Earth's anomalous middle-age magmatism driven by plate slowdown

Abstract: The mid-Proterozoic or "boring billion" exhibited extremely stable environmental conditions, with little change in atmospheric oxygen levels, and mildly oxygenated shallow oceans. A limited number of passive margins with extremely long lifespans are observed from this time, suggesting that subdued tectonic activity—a plate slowdown—was the underlying reason for the environmental stability. However, the Proterozoic also has a unique magmatic and metamorphic record; massif-type anorthosites and anorogenic Rapaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The paucity of eclogites from the mid-Paleoproterozoic essentially until the late Neoproterozoic coincides with the period of low cooling and exhumation rates discussed earlier and is also related to the warmer style of orogenesis associated with the tenure of the supercontinents Columbia and Rodinia (Spencer et al, 2021) and the resulting warmer subcontinental mantle due to continental insulation (Tamblyn et al, 2022a;Zou et al, 2023) and an associated plate slowdown (Sobolev and Brown, 2019;O'Neill et al, 2022). The absence of blueschists prior to the late Neoproterozoic is enigmatic.…”
Section: Eclogites and Secular Change In Metamorphismmentioning
confidence: 67%
See 2 more Smart Citations
“…The paucity of eclogites from the mid-Paleoproterozoic essentially until the late Neoproterozoic coincides with the period of low cooling and exhumation rates discussed earlier and is also related to the warmer style of orogenesis associated with the tenure of the supercontinents Columbia and Rodinia (Spencer et al, 2021) and the resulting warmer subcontinental mantle due to continental insulation (Tamblyn et al, 2022a;Zou et al, 2023) and an associated plate slowdown (Sobolev and Brown, 2019;O'Neill et al, 2022). The absence of blueschists prior to the late Neoproterozoic is enigmatic.…”
Section: Eclogites and Secular Change In Metamorphismmentioning
confidence: 67%
“…The secular trend that emerges from these studies reveals faster cooling/exhumation rates in the Phanerozoic than in the mid-Paleoproterozoic, with a low from the late Paleoproterozoic to the early Neoproterozoic (Zou et al, 2023) that coincides with a dearth of low-T /P metamorphic localities in Mesoproterozoic orogens (Brown et al, 2022). The mid-Proterozoic low is associated with the Columbia and Rodinia supercontinents, where continental insulation (Tamblyn et al, 2022a;Zou et al, 2023) and a plate slowdown (Sobolev and Brown, 2019;O'Neill et al, 2022) reduce the rate of secular mantle cooling leading to a warmer style of orogenesis (Spencer et al, 2021).…”
Section: Cooling and Exhumation -Size And Age Mattermentioning
confidence: 82%
See 1 more Smart Citation
“…These include an apparent high in thermobaric ratios recorded in metamorphic rocks Johnson, 2018, 2019, Figure 1b), and intrusion of voluminous massif anorthosite suites (Ashwal and Bybee, 2017, Figure 1c). It has been proposed that many of these features can be explained by the combined influence of mantle heating due to supercontinental insulation (Brown and Johnson, 2018), a slowdown in plate motions (O'Neill et al, 2022), and a temporary return to a single-lid tectonic regime following an attempted start of plate tectonics in the Paleoproterozoic (Stern, 2020). However, Roberts et al (2022) questioned the necessity for supercontinental insulation and demonstrated that plate tectonics, albeit dominated by accretionary orogenesis, was active throughout the mid-Proterozoic.…”
Section: Introductionmentioning
confidence: 99%
“…Compilation of geologic Earth evolution observations. (A) Reconstructed plate velocities, U p [pink lines,(11); blue lines,(12,13); green lines,(62)]. (B) Mantle potential temperature, T p , inferred from non-arc basalts and komatiites(63,64).…”
mentioning
confidence: 99%